Self-serving leadership and innovative behavior: Roles of psychological entitlement and moral identity - Mao, Hongyi; Peng, Shuai; Zhang, Luni; Zhang, Yajun (Frontiers in Psychology, 2023)
On the basis of social information processing theory, this study proposes a model of the influence mechanism of self-serving leadership (SL) on employee innovative behavior (IB), with psychological entitlement as the mediating variable and moral identity as the moderating variable. The paired data of 82 leaders and 372 employees collected at three time points are analyzed by the hierarchical linear modeling. Results corroborate that SL impairs employee IB. Moreover, the relationship between SL and employee IB is mediated by psychological entitlement. Finally, moral identity has a negative moderating effect of SL on psychological entitlement and an indirect effect on employee IB through psychological entitlement.